What is the European Management School Model? - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2012)
The article discusses the important role of the European Foundation of Management Development (EFMD) in positioning and influencing business schools in Europe. It highlights the effort of the organization in ensuring internationalization and corporate link to high quality management education in business schools. It also mentions the success of the European management schools in emphasizing international character and being agents in the transformation of management education.